Development and Validation of a Food Frequency Questionnaire for Use in Epidemiological Studies Among North Karnataka Population - Deepa S Sajjanar; Indira A Hundekari; Rekha Udgiri; Vijay Warad; Sanjeev L Sajjannar (Medsci Publications, 2024)
Background: Dietary records, such as food diaries (FD) and food frequency questionnaires (FFQs), are widely employed in large-scale epidemiological analyses. Given the regional diversity in dietary habits, this study aimed to develop and assess the reproducibility and construct validity of a novel FFQ tailored for northern Karnataka (FFQ-NK). Methodology: A detailed food list was created based on food use and market surveys in the region. Utilizing data from 24-hour diet recalls and a supplemental focus group discussion, a 116-item semi-quantitative FFQ was developed for adults in north Karnataka. Setting and Subjects: Involving 100 participants from north Karnataka, the FFQ was interviewer administered and the participants also completed three 24-hour dietary recalls (DR), serving as a reference for validity assessment. Results: Though the FFQ indicated higher food and nutrient intake compared to food records. Significant correlations were found for nutrient intake. Pearson's correlation coefficients between FFQs and DRs ranged from 0.717-0.965 (isoflavonols to energy). Conclusions: The developed and validated FFQ is a valuable tool for epidemiological studies requiring nutrient intake estimates in the north Karnataka population. It serves as an effective dietary assessment tool for individuals aged 20 and older in large-scale epidemiological studies.